El producto bruto interno y la tributación interna en los departamentos de la Amazonía Peruana 2008-2022 - Cardama Tang, Olga Adriana (2024)
In 1998, the Peruvian Congress approved the "Law to Promote Investment in the Amazon Region", with the intention of stimulating the sustainable and comprehensive development of the departments of the Peruvian Amazon by establishing the terms for public sector investment and the incentive of private investment. Over time, some taxpayers distorted the purpose of the Act and abused tax incentives, leading to tax evasion and avoidance, among other malpractices. 25 years after said promulgation, with modifications and repeals involved, it is important to analyze if there is any relationship between the amounts generated by economic activities and the amounts collected by internal taxes in the five departments of the Peruvian Amazon. The research was of a quantitative type, correlational level and non-experimental design with panel data. Thus, it was determined that there is a positive relationship of 73.96% between GDP and internal taxation in the departments of the Peruvian Amazon during the period 2008-2022.